Il ruolo della consapevolezza strategica nei processi di crescita delle pmi. Riflessioni teoriche ed evidenze empiriche - Pencarelli, Tonino; Savelli, Elisabetta; Splendiani, Simone (Piccola Impresa / Small Business, 2010)
This paper analyzes strategic awareness and its role in the strategic growth paths of Small and Medium sized Enterprises. The empirical survey shows that local small firms have quantitatively and qualitatively strong growth propensities. They also have several alternatives on the horizon that can be divided into three groups: growth through internationalization, external growth based on strategic alliances, and growth based on innovation - in the broad sense. Generally, local entrepreneus do not have great abilities in correctly recognizing and evaluating the strengths and weaknesses of the corporate system and opportunities and threats in the market system. They are not, therefore, able to identify the most suitable strategic options and the best ways of implementing them. This low degree of strategic awareness means that the growth processes of small enterprises are hampered or distorted, compromising their performance. In the conclusion, we identify some proposals to help small entrepreneurs increase their strategic awareness according to the knowedge management approach.